The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1980-57642013dn70100006
|View full text |Cite
|
Sign up to set email alerts
|

The INECO Frontal Screening tool differentiates behavioral variant - frontotemporal dementia (bv-FTD) from major depression

Abstract: Executive dysfunction may result from prefrontal circuitry involvement occurring in both neurodegenerative diseases and psychiatric disorders. Moreover, multiple neuropsychiatric conditions, may present with overlapping behavioral and cognitive symptoms, making differential diagnosis challenging, especially during earlier stages. In this sense, cognitive assessment may contribute to the differential diagnosis by providing an objective and quantifiable set of measures that has the potential to distinguish clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 39 publications
(54 reference statements)
0
40
0
4
Order By: Relevance
“…We used the Institute of Cognitive Neurology (INECO) Frontal Screening test (IFS; Torralva et al, 2009b ), which assesses frontal lobe function as indexed by the following subtasks: motor programming, conflicting instructions, Verbal Inhibitory Control, Abstraction Ability (proverbs interpretation), Backward Digit Span, Spatial Working Memory, and Go/NoGo. This task has been used with different neuropsychiatric populations ( Torralva et al, 2009b , 2012 ; Fiorentino et al, 2013 ; Baez et al, 2014b ) A mean total score is calculated from the sum of the subtask scores (30 points). A 25-point cutoff score has shown a sensitivity of 96.2% and a specificity of 91.5% in detecting patients with dysexecutive syndrome ( Torralva et al, 2009b ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the Institute of Cognitive Neurology (INECO) Frontal Screening test (IFS; Torralva et al, 2009b ), which assesses frontal lobe function as indexed by the following subtasks: motor programming, conflicting instructions, Verbal Inhibitory Control, Abstraction Ability (proverbs interpretation), Backward Digit Span, Spatial Working Memory, and Go/NoGo. This task has been used with different neuropsychiatric populations ( Torralva et al, 2009b , 2012 ; Fiorentino et al, 2013 ; Baez et al, 2014b ) A mean total score is calculated from the sum of the subtask scores (30 points). A 25-point cutoff score has shown a sensitivity of 96.2% and a specificity of 91.5% in detecting patients with dysexecutive syndrome ( Torralva et al, 2009b ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the usefulness of one screening tool specifically designed to probe executive functions: the IFS [22,26,27,29]. Here, we examine the properties of the IFS as an executive screening test for patients with RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this brief screening test probes executive functions in particular, and it provides useful information about frontal functioning by tapping different executive processes, such as verbal and motor inhibitory control, verbal and visual working memory, and abstraction ability, among others. It has also been shown useful in the detection of executive dysfunction in other neurological and psychiatric conditions such as unipolar depression [26], bipolar disorder, and attentional and hyperactivity disorder [27]. Several studies have already reported on the usefulness of this instrument in different populations, reporting relatively high levels of specificity and sensitivity for a screening tool [22], along with a higher ability than other executive screening tools to discriminate between different types of dementia [28], between dementia and depression [26], and to detect executive dysfunction in patients with attention deficit disorder [21,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W zamyśle autorów testu IFS jest narzędziem oceny funkcji wykonawczych w chorobach neurodegeneracyjnych [24]. Znajduje ponadto zastosowanie w diagnostyce dysfunkcji wykonawczych w psychiatrycznych jednostkach chorobowych -schizofrenii, depresji, chorobie afektywnej dwubiegunowej, ADHD [25][26][27].…”
Section: Metody Przesiewoweunclassified